Early marriage of girls among the scholars of Sharia and law - Mohammed, L.Kamran Jamal (Sulaimani Journal for Humanities, 2026)
There is no doubt that one of the questions that lawyers and scholars of Sharia often face is the marriage of girls by their guardians before they reach the age of puberty Tazor still exists and people suffer from it in some way, and often public custom is blamed for this, and often religious texts and legal provisions are blamed. There are many different and contradictory opinions on this issue. Therefore, the scholars are divided into two groups: some believe that this type of marriage is permissible, others say that it is not permissible They rely on the hadiths of the Messenger of Allah (peace and blessings of Allah be upon him) and his actions and the events that we have received from his Companions I thought it important to explain this issue in an intensive manner, and I felt that it expressed strong opinions. After reading the article, I found that the research needs to be divided into three topics as follows: The first topic: The purpose and meaning of marriage and early divorce from the perspective of Shari'ah and law. Second: The opinion of the scholars of Shari'ah and law on the marriage of minors and their proofs. Chapter 3: Interpretation and evaluation of the evidence and identifying the author's strong opinion. We conclude by discussing the most important points we have made while writing this paper, along with recommendations
Keywords: Marriage; Immature; Collection of Scholars; Ibn Shubrum